HUBUNGAN SENGKETA DALAM CV STABILITAS OPERASIONAL PERUSAHAAN - Juhana Nuryana; Pandri Zulfikar; Rifqi Syifa’ul Qolbi; Muslimin; Hikmat Ansori; Dian Retno Widayati (Berajah Journal, 2026)
Commanditaire Vennootschap (CV) is a commercial partnership with unique characteristics involving the separation of roles between managing partners and limited partners. Disputes arising within CV, whether internal or external, significantly impact company operational stability. This study aims to analyze the causal relationship between disputes in CV and company operational stability, and to evaluate effective dispute resolution mechanisms in maintaining business continuity. The research method used is normative legal research with conceptual and statutory approaches. The results indicate that internal disputes between managing partners and limited partners, typically stemming from unclear authority distribution under Article 20 of the Commercial Code, negatively affect financial stability, company reputation, and internal partner relationships. External disputes with third parties, particularly regarding breach of contract and industrial relations disputes, cause operational disruptions, decreased productivity, and financial losses. This study recommends strengthening Alternative Dispute Resolution (ADR) mechanisms, clarifying cooperation agreements, and implementing periodic audits as risk mitigation strategies for CV disputes.